Politicisation ‘Reversed’: EU Free Trade Negotiations with West Africa and the Caribbean - Moerland, Anke (2020)
The politicisation of recent European Union (EU) trade negotiations such as the Transatlantic Trade and Investment Partnership or the Comprehensive and Economic Trade Agreement suggests that the more negotiations focus on deep integration issues, the higher the potential for polarization of values and interests. Yet, as we argue, this pattern does not necessarily hold true in EU trade negotiations with the developing world. In the case of the Economic Partnership Agreements with West Africa and the Caribbean region, the pattern of politicisation was ‘reversed’: Politicisation remained low in the Caribbean region, despite the inclusion of deep integration issues. To the contrary, negotiations became highly politicised in West Africa, where negotiations focussed on the traditional realm of trade in goods. Combining the insights from the literature on the role of non-state actors (NSAs) in trade policy-making in developing countries and on politicisation, we show that limited pre-existing mobilisation resources of NSAs, and few opportunities to engage with the political level of negotiations, imply that those affected by the inclusion of deep integration issues hardly mobilise. We also find that lack of technical expertise and the significance of traditional trade areas pre-empts NSAs from engaging in emotive framing on deep integration issues. This helps us to unpack the different patterns of politicisation across both regions: Politicisation in West Africa was facilitated by civil society actors who—in contrast to the Caribbean region—could draw on pre-existing networks, expertise, and direct access to the regional negotiation level.